Climatological Review of Enugu Rainfall from 1916 a 2012 and its Implications (Global Journal of Science Frontier Research, 2016)
The study Climatological Review of Enugu Rainfall (RF) from 1916 -2012 and Its Implications examines in detail the RF characteristics and pattern over Enugu during the study period. These include the annual, seasonal and parameters like onset, cessation, duration and seasonality of Enugu RF. Data for this work were extracted from the Nigerian Meteorological Agency (NIMET) Oshodi, Lagos archive for analysis. The result shows among other things that RF fluctuates both annually and seasonally between and outside the group study period over Enugu. In annual / trend analysis it was observed that RF occurrence decreased from 1916 -1991 generally, but from 1991 -2012 RF tend to increase. It was also observed that wet season accounted for 83.30% of the total RF over Enugu. The wet season months accounted for 83.30% of the total RF over Enugu.
Keywords: climate change and fluctuation; rainfall parameters; seasonality index of rainfall; wet and dry season; enugu